Structural Design and Analysis for Leaf Spring Type Axial Compliant Mechanism of Scroll Compressor - Tang, Yuehju; Hung, Chinghua; Shen, Biende; Chang, Yuchoung; Hu, Robert Yie-Zu (My University, 2009)
There are many factors can influence the efficiency of scroll compressor, and one of them is the internal leakage. However, the traditional function to avoid internal refrigerant leakage in scroll pump is designing a compliant mechanism for dynamically sealing the scroll clearance caused by the unbalance inner forces and moments in scroll compressor. As we know, that the leakage path has been determined while the scroll line length has been designed. Axial leakage would be larger than flank leakage because of its longer leakage path. This paper discussed a compliant mechanism called leaf spring type axial compliant mechanism, which could improve the volumetric efficiency and increase the cooling capacity. The compliance mechanism used on controlling the floating tolerance of fixed scroll and keeping an optimum axial leakage. For the incongruity backpressure on fixed scroll in the axial direction, more friction loss comes of the increasing force pushing on the fixed scroll to contact with the orbiting scroll and decrease the compressor efficiency. For eliminate the unnecessary loss, this paper take case study of designing an axial compliance leaf spring structure to limit the floating distance of fixed scroll and keep the tip clearance under the optimum value. From finite element analysis and prototype test, this new module of sealing function could bring lower noise and higher cooling performance.
Keywords: low-side type; scroll compressor; axial compliance; high cooling capacity; limited position; leaf spring